Marketing research - McDaniel, Carl (John Wiley and Sons, 2005)
Presents marketing research through the eyes of a manager using and purchasing research information, while maintaining solid, competitive coverage of quantitative methods. Extensive updates and revisions enhance its traditional high quality and enjoyable style.